2017
DOI: 10.1002/jum.14513
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values for Tonsils in Pediatric Populations Based on Ultrasonography

Abstract: These normal tonsillar sizes on transcervical ultrasound in pediatric patients can be used to diagnose tonsillar lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Similarly, Wang et al study reported a larger objective tonsil volume in obese children compared with control participants. However, a study by Hong et al that used USG reported that the tonsil dimension and volume increased with age but not with weight or height. According to these results, more research is necessary about the effect of obesity on tonsil volumes, and USG can be used for this purpose.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Wang et al study reported a larger objective tonsil volume in obese children compared with control participants. However, a study by Hong et al that used USG reported that the tonsil dimension and volume increased with age but not with weight or height. According to these results, more research is necessary about the effect of obesity on tonsil volumes, and USG can be used for this purpose.…”
Section: Discussionmentioning
confidence: 96%
“…Although computed tomography and magnetic resonance imaging have been reported to have successful results, especially in the diagnosis of peritonsillar abscesses, the use of those methods is limited because of radiation exposure, sedation necessity in children, and high costs. Ultrasonography (USG) has been used in only a limited number of studies of tonsil tissue assessments despite high patient compliance, low cost, and its nonradioactive nature . Also, those studies included only the pediatric population.…”
mentioning
confidence: 99%
“…The Philips iU 22 machine (Philips Healthcare, DA Best, The Netherlands) with a 12–5 MHz linear transducer and GE E10 machine (GE Healthcare, Milwaukee, WI) with a 9 L linear transducer performed the transcervical US. First, referring to the measuring this method described by Hong HS, 7 we acquired the transverse diameter ( T ), anteroposterior diameter (AP), and length ( L ) of each palatine tonsil. The transducer was placed in the submandibular space.…”
Section: Methodsmentioning
confidence: 99%
“…Since Coquia SF 6 tried to perform a US examination of the oropharynx in 2015, scholars have attempted to use the US to carry out the tonsillar examination in children. [7][8][9][10] Due to the impact of tonsillar hypertrophy on airway obstruction, scholars are more concerned with the study of tonsillar hypertrophy. However, the use of US to tonsillar hypertrophy is still in the primary stage; most scholars tried to explore the normal values in normal children to evaluate tonsillar hypertrophy and improve the diagnosis and treatment of patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation